Estimating Dining Plate Size From an Egocentric Image Sequence Without a Fiducial Marker - Jia, Wenyan; Wu, Zekun; Ren, Yiqiu; Cao, Shunxin; Mao, Zhi-Hong; Sun, Mingui (Frontiers in Nutrition, 2021)
Despite the extreme importance of food intake in human health, it is currently difficult to conduct an objective dietary assessment without individuals’ self-report. In recent years, a passive method utilizing a wearable electronic device has emerged. This device acquires food images automatically during the eating process. These images are then analyzed to estimate intakes of calories and nutrients, assisted by advanced computational algorithms. Although this passive method is highly desirable, it has been thwarted by the requirement of a fiducial marker which must be present in the image for a scale reference. The importance of this scale reference is analogous to the importance of the scale bar in a map which determines arbitrary distances or areas in the geological region covered by the map. Likewise, the sizes or volumes of arbitrary foods on a dining table covered by an image cannot be determined without the scale reference. Currently, the fiducial marker (often a checkerboard card) serves as the scale reference which must be present on the table before taking pictures, requiring human efforts to carry, place and retrieve the fiducial marker manually. In this work, we demonstrate that the fiducial marker can be eliminated if an individual’s dining location is fixed and a one-time calibration using a circular plate of known size is performed. When the individual uses another plate of an unknown size, our algorithm estimates its radius using the range of pre-calibrated distances between the camera and the plate from which the desired scale reference is determined automatically. Our comparative experiment indicates that the mean absolute percentage error of the proposed estimation method is approximately 10.73%. Although this error is larger than that of the manual method of 6.68% using a fiducial marker on the table, the new method has a distinctive advantage of eliminating the manual procedure and automatically generating the scale reference.